2012
DOI: 10.1080/17408989.2012.726977
|View full text |Cite
|
Sign up to set email alerts
|

Models-based practice: great white hope or white elephant?

Abstract: Structured AbstractBackground: Many critical curriculum theorists in physical education have advocated a modelor models-based approach to teaching in the subject. This paper explores the literature base around models-based practice (MBP) and asks if this multi-models approach to curriculum planning has the potential to be the great white hope of pedagogical change or, if in fact, it is a white elephant that should be reconsidered or abandoned.Purpose: To review the literature around pedagogical and curricular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
161
0
28

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(192 citation statements)
references
References 58 publications
3
161
0
28
Order By: Relevance
“…As a result, TGf U may have little meaning for teachers (Stolz and Pill, 2014). In using this model over a number of years based on his own students' needs, Pete supports the view that learning how to use TGf U knowing the students' needs would almost certainly improve the effectiveness of the approach's adoption (Brooker et al, 2000;Butler and Griffin, 2010;Casey, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, TGf U may have little meaning for teachers (Stolz and Pill, 2014). In using this model over a number of years based on his own students' needs, Pete supports the view that learning how to use TGf U knowing the students' needs would almost certainly improve the effectiveness of the approach's adoption (Brooker et al, 2000;Butler and Griffin, 2010;Casey, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, teachers' learning how to use TGf U in their own school based on their students' needs would almost certainly improve the effectiveness of the approach's adoption (Butler and Griffin, 2010;Casey, 2014). Indeed, Stolz and Pill (2014) have argued that PCK is context specific and in ignoring the contextual features that teachers face on a day-to-day basis means that innovations such as TGf U has little meaning for them.…”
Section: Teacher Benchmarksmentioning
confidence: 99%
“…Cooperative Learning (CL) (Dyson and Casey 2012) or Sport Education (SE) (Siedentop 1994), taught in isolation. The somewhat limited subject-wide use of MBP has been attributed to the challenges teachers face when using MBP (Casey 2014;Metzler 2011). At the core of these challenges is the admission by teachers that they lack experience, confidence and competence using MBP and therefore return to their traditional practices (Casey 2014;Gurvitch and Blankenship 2008) after an initial period of innovation has passed (Goodyear and Casey 2015, 186).…”
mentioning
confidence: 99%
“…Metzler (2011) describes pedagogical models as blueprints for PE teaching, learning and assessment where each model has distinctive teaching and learning objectives. Casey (2014) suggested that while MBP has begun to help PE teachers to change and develop their pedagogies and curriculum we still do not fully understand the impact of changing to a MBP. Furthermore, advocates of MBP practice need to explore the pedagogical and curricular ramifications on teachers of the long-term adoption of a MBP.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Mosston's Spectrum of Teaching Approaches (Mosston, 1966;Mosston & Ashworth, 2008) is an example of one of these enduring ideas. More recently, however, scholarly and research literature has been promoting models based practice (MBP), particularly as a means for implementing student-centred approaches to learning (Casey, 2014;Hastie & Casey, 2014). Metzler (2011) describes pedagogical models as blueprints for PE teaching, learning and assessment where each model has distinctive teaching and learning objectives.…”
Section: Introductionmentioning
confidence: 99%